Approaches to using information technology facilities in foreign language instruction - Zaitseva, Natalia; Зайцева, Наталя Володимирівна; Зайцева, Наталья Владимировна (My University, 2017)
Tthe article is devoted to the problem of media and informative literacy forming. The importance of information technology using in foreign language instruction is stressed.
Keywords: society informatization; information technologies; professional foreign language; competence; информатизация общества; компетенция; информационные технологии; профессионально-ориентированный иностранный язык